FORMATION OF A CLUSTER BUSINESS DEVELOPMENT MECHANISM IN UKRAINE IN MODERN CONDITIONS - Voloshko, Kateryna A. (Journal of Strategic Economic Research, 2025)
The article presents the results of a study on the formation of an organizational mechanism for cluster business development in Ukraine in modern conditions. It is proved that for effective management of entrepreneurship development in Ukraine, first of all, a developed innovation infrastructure is necessary. Such infrastructure assumes the presence of a market for innovations, a market for investments in innovative activities and a market for innovation competition, that is, competition between business entities that introduce innovations, new technologies, etc. at their own production facilities. It is substantiated that a feature of the innovative path of development is the formation of system-forming "profit centers" and clustering of critical industries in the plural, and not just separately. This will allow diversifying the economy, stimulating the innovative activity of market participants in many promising innovative areas at once. The study identified the following features that influence the formation of the cluster business development mechanism: development of innovation processes; development of the organizational and technical potential of the business, covering the main activity, support structures and service units; product renewal, which ensures an increase in the level of readiness of production for the release of new products and the level of organization of the implementation of innovative projects.